Useful publication - A. I. Kudryashov (Известия высших учебных заведений: Геология и разведка, 2022)
This article provides a review of the book co-authored by P.A. Ignatov and K.V. Novikov entitled “Field diagnostics of tectonic disturbances and fluid-fracturing formations in kimberlite-containing deposits of the lower Paleozoic” (Mirny: ALROSA, 2019). The book describes a new technique for core sample documentation (along with the conventional technique). The described prospecting wells were drilled within the Nakyn kimberlite field of the Yakutsk diamondiferous province. Of particular interest is the detailed classification and characteristics of tectonic, magmatic, fluid-fracturing and mineralogical features, which contributes to the reliability of kimberlite bodies forecasting. The proposed technique can be used to document core samples from wells of other utility types.